PENENTUAN RASIO MOL REAKTAN OPTIMAL PADA PEMBUATAN SURFAKTAN DIETANOLAMIDA DENGAN KATALIS NATRIUM HIDROKSIDA (NaOH) - Pevi Riani (Politeknik ATI Padang, 2018)
Surfactant is a molecule which also has a hydrophilic group and a lipophilic group so that it can unite a mixture consisting of water and oil. Diethanolamide is a nonionic surfactant that is widely used in the manufacture of various cleaning, care and cosmetics products. This surfactant is renewable and easily degraded so it does not pollute the environment. In this study, we will observe the effect of the mole ratio the reactants on the synthesis of dietanolamide surfactants from dietanolamine and methyl ester of fatty acids of palm distillate (ALSD) with sodium hydroxide (NaOH) catalyst. This study aims to determine the value of Hydrophylic Lipophylic Balance (HLB), saponification number, acid number, ester number of surfactant by observing the influence of mole ratio of reactants. This research was conducted using hot plate Carousel at a temperature of 80°C, reaction time of 4 hours, the ratio of moles of reactants, among others (1: 1, 1: 2, 2: 1, 2: 2, 3: 1, 3: 2), stirring speed 300 rpm and catalyst concentration 1% (b/b). In the oxidation reaction the sample is taken after hours then the results are washed with n-hexane then purified by heating the surfactant product at a temperature of 90°C to vaporize the hexane solvent. The results containing surfactants were analyzed by Hydrophylic Lipophylic Balance Method and FT-IR Spectrophotometer. Based on this study, optimal conditions were obtained at 80°C, 4 hours reaction time and 3: 2 mole ratio reactants. From the results of analysis of dietanolamide surfactant obtained HLB value is 5.81 which is in the range of HLB emulsifier water in oil according to the standard.